Merohedral Mechanism Twining Growth of Natural Cation-Ordered Tetragonal Grossular - Taras L. Panikorovskii; Irina O. Galuskina; Vladimir N. Bocharov; Vladimir V. Shilovskikh; Evgeny V. Galuskin (Crystals, 2022)
Garnet supergroup minerals are in the interest of different applications in geology, mineralogy, and petrology and as optical material for material science. The growth twins of natural tetragonal grossular from the Wiluy River, Yakutia, Russia, were investigated using single-crystal X-ray diffraction, optical studies, Raman spectroscopy, microprobe, and scanning electron microscopy. The studied grossular is pseudo-cubic (a = 11.9390 (4), c = 11.9469 (6) Å) and birefringent (0.01). Its structure was refined in the Ia3¯d, I41/acd, I41/a, and I4¯2d space groups. The I41/a space group was chosen as the most possible one due to the absence of violating reflections and ordering of Mg2+ and Fe3+ in two independent octahedral sites, which cause the symmetry breaking according to the group–subgroup relation Ia3¯d → I41/a. Octahedral crystals of (H4O4)4−-substituted grossular are merohedrally twinned by twofold axis along [110]. The mechanism of twining growth led to the generation of stacking faults on the (110) plane and results in the formation of crystals with a long prismatic habit.